Modelling of Jatropha Oil Hydrocracking in a Trickle-Bed Reactor to Produce Green Fuel - Yuswan Muharam; null Dianursanti; Andrey Sapati Wirya (International Journal of Chemical Engineering)
Trickle-bed reactor (TBR) modelling to produce green fuel via hydrocracking of jatropha oil using silica-alumina-supported Ni-W catalysts was performed in this research. The objectives of this study are to obtain a TBR with good heat transfer and the optimum condition for high purities of products. A two-dimensional axisymmetric model with a diameter of 0.1 m and a length of 10 m was used as a representative of the actual TBR system. Heterogeneous phenomenological models were developed considering mass, energy, and momentum transfers. The optimisation was conducted to obtain the highest green fuel purity by varying catalyst particle diameter, inlet gas velocity, feed molar ratio, and inlet temperature. The simulation shows that a TBR with an aspect ratio of 100 has achieved a good heat transfer. The diesel purity reaches 44.22% at 420°C, kerosene purity reaches 21.39% at 500°C, and naphtha purity reaches 25.30% at 500°C. The optimum condition is reached at the catalyst diameter of 1 mm, the inlet gas velocity of 1 cm/s, the feed molar ratio of 105.5, and the inlet temperature at 500°C with the green fuel purity of 69.4%.